B Group Vitamins Current Uses and Perspectives - Guy LeBlanc, Jean; Savoy de Giori, Graciela (IntechOpen, 2018)
B-group vitamins are involved in numerous metabolic reactions and their widespread deficiency can cause a large series of health problems. The aim of this book is to provide an update on the current use and perspectives of B-group vitamins. Novel methods to detect folates in pregnant women, the use and role of folate dentistry, the use of genotype notification to modify food intake behavior, thiamin metabolism in Archaea and its role in plants and in crop improvement, the use of riboflavin in blood safety and niacin in metabolic stress and resistance in dairy cows are some of the subjects that are described in this multitopic book written by authors from seven different countries.